THE PUBLISHER'S PERSPECTIVE ON JOURNAL AND BOOK PUBLISHING. - NAHLEN, DAWN; CLARK, SANDRA (Seminars in Oncology Nursing, 2018)
OBJECTIVES: To provide information about the publisher's perspective on journal and book publishing. DATA SOURCES: Online publishing resources, data analytics, personal experience. CONCLUSION: Publishers provide vital tasks that support the publishing process, such as managing submissions, facilitating peer review, and manuscript editing. Publishers offer supportive and online resources, promote books and journals, and maintain archives that serve as a record of science for posterity. IMPLICATIONS FOR NURSING PRACTICE: Many nurse authors are not fully aware of the publishers' role in the publishing process, the services they provide, and the resources they offer. Knowledge and understanding of the role of the publisher can strengthen the author--publisher partnership.